Persepsi Masyarakat Terhadap Lokalitas Program Acara Televisi Swasta Lokal (Studi Kasus Persepsi Masyarakat Kota Madiun terhadap Lokalitas Program Acara Dagelan Tembang Jawa (D'Tejo) Sakti Madiun TV) - Safitri, Elixia Alifatul, Drs. Joko Sutarso, SE, M.Si, Rinasari Kusuma, M.I.Kom (2016)
In Indonesia, there are two broadcasters hold radio broadcasting services or television broadcasting services, namely, the network broadcasting station or a local broadcasting station. Local private television presence gives large influence to people's lives in the areas of political, economic, social, and cultural. This study aims to determine how the public perception in Madiun City to locality slapstick Song Java programs ( D' Tejo ) Sakti TV Madiun. This research is a case study. Data collection techniques used were interviews semistuktur and documentation. The data source using purposive sampling with three categories of informants , informants education experts , expert informants and informant audience art workers . The study is concluded that the presence of Sakti TV Madiun basically has to be accepted by people in Madiun although it still needs to be maximized . Song slapstick Java ( D' Tejo ) as a flagship program of Sakti TV Madiun also favored by many people in Madiun , just still require updates that are not impressed monothone concept. Renewal concept in this case should be emphasized in Madiun city of the culture and a way to develop that culture.